Kemanjuran Strategi Mind-Mapping untuk Meningkatkan Keterampilan Berpikir Kreatif dalam Pengambilan Keputusan Karier Siswa - Nur Hidayah; M Ramli; Lutfi Fauzan (Indonesian Journal of Educational Counseling, 2019)
THE EFFECTIVENESS OF MIND-MAPPING STRATEGY TO IMPROVE CREATIVE THINKING SKILLS IN STUDENT CAREER DECISION MAKING. The disruptive era in industrial revolution 4.0 is vital for students. In this era, students need creative thinking skills, especially in making career decisions. The Mind Mapping strategy is the right choice to train students' creative thinking skills. This creative thinking skills training is intended for students of Malang State High School Laboratory, class XII MIPA, IPS, IBB, and ICP. The expected goal is to increase the creative thinking skills of Malang State University High School Laboratory students in their career decision making. Based on the results of the study showed that creative thinking skills in career decision making before and after being trained with mind-mapping strategies, there was a significant increase. The Wilcoxon test results were Z = 4,644 with a significance of 0,000. That is, there are significant differences in creative thinking skills in student career decision making before and after being trained with mind-mapping strategies.